Performing history : theatrical representations of the past in contemporary theatre - Rokem, Freddie, 1945- (Studies in theatre history and culture., 2000)
In his examination of the ways in which theatre participates in the ongoing representations of and debates about the past, Freddie Rokem concentrates on the ways in which theatre after World War II has presented different aspects of the French Revolution and the Holocaust, showing us that by "performing history" actors bring the historical past and the theatrical present together.